Everyday heroes - Johnson, Beth 1956- (Townsend Press, 2003)
Profiles twenty young men and women of a variety of ethnic backgrounds whose courage and determination have helped them overcome such obstacles as poverty, racism, abuse, neglect, illness, and drugs.